Pheromone of the Banana-Spotting Bug, Amblypelta lutescens lutescens Distant (Heteroptera: Coreidae): Identification, Synthesis, and Field Bioassay - Ashot Khrimian; Harry A. C. Fay; Filadelfo Guzman; Kamlesh Chauhan; Chris Moore; Jeffrey R. Aldrich (Psyche: A Journal of Entomology)
The banana-spotting bug, Amblypelta lutescens lutescens Distant (Heteroptera: Coreidae), is one of the principal pests of tree fruits and nuts across northern and eastern Australia. Apart from visual damage assessment, there are currently no reliable methods for monitoring bug activity to aid management decisions. An attractant pheromone for this species that could be used as a trap lure could potentially fill this void. Earlier, two male-specific compounds were identified in airborne extracts from A. lutescens lutescens, (E,E)-α-farnesene and (R,E)-nerolidol; an unknown compound with a molecular weight 220 was also detected. We now report the identification of this hitherto unknown compound as (R,E,E)-α-farnesene-10,11-oxide. Synthesis of this epoxide was conducted using a regioselective asymmetric dihydroxylation of a sulfolene. A blend mimicking the natural proportions of (E,E)-α-farnesene, (R,E)-nerolidol, and (R,E,E)-α-farnesene-10,11-oxide attracted male and female A. lutescens lutescens as well as nymphs in the field, verifying that the aggregation pheromone comprises or is contained within this group of compounds.